African Womanhood and Incontinent Bodies Kenyan Women with Vaginal Fistulas - Gatwiri, Kathomi (Springer Nature Singapore : Imprint: Springer, 2019)
This book reveals the structures of poverty, power, patriarchy and imperialistic health policies that underpin what the World Health Organization calls the "hidden disease" of vaginal fistulas in Africa. By employing critical feminist and post-colonial perspectives, it shows how "leaking black female bodies" are constructed, ranked, stratified and marginalised in global maternal health care, and explains why women in Africa are at risk of developing vaginal fistulas and then having adequate treatment delayed or denied. Drawing on face-to-face, in-depth interviews with 30 Kenyan women, it paints a rare social portrait of the heartbreaking challenges for Kenyan women living with this most profound gender-related health issue - an experience of shame, taboo and abjection with severe implications for women's wellbeing, health and sexuality. In absolutely groundbreaking depth, this book shows why research on vaginal fistulas must incorporate feminist understandings of bodily experience to inform future practices and knowledge.